A Learning Community for New Chairs - Lynn Stallings; Meghan Burke; Ruth A. Goldfine; Dawn L. Kirby; Monica Nandan; Sharon Pearcey; Kandice Porter; Amy Woszczynski (Academic Chairpersons Conference Proceedings, 2015)
Key elements of an effective professional learning community will be discussed, including readings, peer mentoring, meeting structure, composition, and timing of topics. Presenters will discuss the challenges of their first years as chairs, particularly finding their individual leadership styles and a balance between professional and personal lives.
Keywords: New chairs development; Professional learning community; Mentoring; Professional development for chairs; Cross-disciplinary learning community; Women in the workplace; Women’s leadership; Work and life balance